Prehospital Emergency Care for Traumatic Brain Injury Patients in Hanoi: A Multicenter Study of Outcomes and Quality of Care - Bui Hai Hoang; Thi Linh Tran; Thanh Nguyen; Quoc Chinh Luong; Michael M. Dinh (Emergency Medicine Australasia, 2026)
ABSTRACT Objective Evaluate prehospital care quality and outcomes for traumatic brain injury ( TBI ) patients in Vietnam. Methods We conducted a retrospective multicentre audit at three tertiary Hanoi hospitals (January–August 2025), including adults with moderate–severe TBI . Prehospital care was assessed against five EPIC ‐ TBI standards and in‐hospital mortality recorded. Results Of 80 cases, 45 (56.3%) were transported by EMS ; 14 (17.5%) received oxygen or saturation monitoring and 11 (13.8%) had blood pressure management. In‐hospital mortality was 22/80 (27.5%), with 14/22 (63.6%) of deaths potentially preventable. Conclusion Major prehospital TBI care gaps support the need for enhanced resources, training and quality assurance.